Ukrainian social investment fund: project concept note (draft) - Yashko, Natalja (Socialinė teorija, empirija, politika ir praktika, 2001)
The goal of the paper is to present the project concept of Ukrainian social investment fund. The reasons for the establishment of the fund are laid down in the first part of the paper. The project concept is described in the second part. The goals, components, targeted beneficiaries, micro-projects eligible for the funding, project targeting, micro-project selection criteria are presented. The implementation of the project is presented in the third part. There are two phases: pilot project and main investment project. The main objective of the pilot project will be preparation of the main USIF project by elaborating mechanisms and building capacity. The monitoring system of the project is presented in the fifth part. The expected outputs/benefits are discussed in the last part.